Odpowiedzialność dyscyplinarna sędziów sądów powszechnych w świetle polskiego ustawodawstwa a wyrok Europejskiego Trybunału Sprawiedliwości Unii Europejskiej z 5 czerwca 2023 r. wydany w sprawie C 204/21 - Belińska, Katarzyna (Uniwersytet Wrocławski Koło Doktryn Politycznych i Prawnych, 2023)
This article presents a brief description of disciplinary liability and the current regulations governing disciplinary liability of judges adjudicating in common courts. In addition, this publication presents the key problems occurring on the canvas judgment of the Court of Justice of the European Union of 5 June 2023 in case C 204/21.
Keywords: disciplinary liability of judges; general clauses; impacts of CJEU judgments